Nature reserve fund of Ukraine: territories and objects of national significance. - K.: LLC "Center for Environmental Education and Information", 2009. - 332 p. (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Nature reserve fund of Ukraine: territories and objects of national significance. - K.: LLC "Center for Environmental Education and Information", 2009. - 332 p.